Odnos med prepričanji in spoprijemanjem z negativnimi čustvi v razredu pri učiteljih osnovne šole - Šimonka, Zita; Košir, Katja (Revija za elementarno izobraževanje, 2014)
Relationship between Beliefs and Basic School Teachers’ Coping with Negative Emotions in the Classroom. Clinging excessively to the myths about the ideal teacher leads into teacher’s excessive expectations, which in consequence leads to burnout and the emergence of negative feelings (Bečaj, 1990). The purpose of this paper is to examine the connection between agreeing with the myths about good teacher and negative emotional experiences and the correlation between self-assessed fitness to the myth of the good teacher and negative emotional experiences. The study involved 137 teachers in basic school. The results showed that teachers excessively cling to myths about good teacher and that on average they all to a certain extent experience negative emotions in the classroom. They most frequently look for reasons of the negative emotions in student behaviour. In the discussion we have suggested some possible solutions that could help teachers cope with negative emotions in the classroom.
Keywords: teachers; negative emotions; beliefs; expectation